Facilitating transitions in language development for children using AAC - Paul, R. (AAC: Augmentative and Alternative Communication, 1997)
Several major transitions in language use take place during the first 5 years of life. Each transition allows the child to move to a higher level of complexity of expression and to accomplish communicative goals more flexibly and precisely than was done at the previous level. At least three of these transitions appear to be modulated to some degree by speech. In the first transition, prellnguistic to early linguistic communication, babbling provides the infant with a prelinguistic form of vocal behavior that is in many ways analogous to language. A second transition takes place in the movement from single words to multiword combinations. In the process of this transition, word order becomes a means by which children convey semantic role information, and transitional forms such as successive one-word utterances help to facilitate the child's leap from single-word speech to multiword sentences. A third transition involves the development of phonological awareness, an important basis for the acquisition of literacy, which builds on the foundation laid by the phonological system for articulation. In each of these transitions, speech appears important for mediating the move to a higher language level. This paper considers the question of how these transitions can be facilitated in children who use augmentative and alternative communication rather than speech as a first expressive system, in order to provide as precise and flexible a communication modality as possible to children with severe speech impairments.
Keywords: Augmentative and alternative communication (AAC); Biocommunications; Children with severe speech and physical impairments; Language acquisition; Linguistics; Pediatrics; Speech; dept.cmd